A smartphone application as a promising tool for large-scale collection of participant data on fertility treatment - Ryo Yokomizo; Tsuguhiko Kato; Kevin Y. Urayama; Akari Nakamura; Makoto Sato; Risa Nasu; Maaya Hine; Hiroshi Kishi; Haruhiko Sago; Aikou Okamoto; Akihiro Umezawa (Scientific Reports)
Abstract In Japan, there is a registry for fertility treatment (the JSOG registry), which is a system that only registers select clinical data related to assisted reproductive technology (ART). This system does not include patient-derived data, so innovative tools that can complement the shortcomings of the existing registry may be useful. In this study we explored the potential of using a smartphone application platform to collect clinical data from patients directly. We recruited participants using the smartphone application “Luna Luna” and requested information that is typically gathered during a medical checkup, including basic physical characteristics, medical history, and results of fertility examinations such as hormone levels and semen analysis. We also asked the participants about the most recent fertility treatment they received and the details of the treatment. We recruited more than 13,000 participants within Japan nationwide in one month, and successfully collected information that is necessary in clinical practice for fertility treatment. Furthermore, through the participants, we were able to obtain information concerning their partners. We gained an expanded understanding of the circumstances surrounding fertility tests performed in Japan and details of fertility treatment such as ovarian stimulation and pregnancy outcomes by each fertility treatment method. This smartphone application has the potential as a promising tool for doctors and couples for information management during fertility treatment.